Do Associations Between Alcohol Use and Alcohol Use Disorder Vary by Weight Status? Results From the National Epidemiologic Survey on Alcohol and Related Conditions‐III. (21st May 2019) - White, Gretchen E.; Richardson, Gale A.; Mair, Christina; Courcoulas, Anita P.; King, Wendy C.
Abstract : Background: Understanding whether the associations between alcohol use and alcohol use disorder (AUD) differ by weight status may be useful in screening for AUD in populations where obesity is common. We aimed to determine whether the associations between alcohol use and AUD differ by weight status. Methods: A total of 24, 869 adult participants of the National Epidemiologic Survey on Alcohol and Related Conditions‐III with a body mass index ≥18.5 kg/m 2 who reported past‐year alcohol use were included. The AUD and Associated Disabilities Interview Schedule‐5 were administered to identify past‐year AUD. Logistic regression was used to test the associations between weight status and levels and patterns of alcohol use with AUD; interactions between weight status and alcohol use variables in relation to AUD were examined. Analyses were stratified by gender. Results: For males and females, the odds of AUD were higher with greater frequency of any alcohol use and heavy drinking, higher average quantity of drinks per drinking day, and past‐year high‐risk drinking. Among males, at the same average quantity of drinks per drinking day, frequency of heavy drinking, or presence of high‐risk drinking, those with class 3 obesity had higher odds of AUD versus lower classes or no obesity ( p for all interactions <0.01). Among females, at the same frequency of any alcohol use, those with healthy weight had the highest odds of AUD, while females with class 3 obesity had the lowest odds of AUD ( p for interaction <0.001); interactions between weight status and other alcohol use variables were not significant ( p ≥ 0.05). Conclusions: The associations between some measures of alcohol use and AUD differed by weight status, with inconsistent results between males and females. Alcohol use thresholds typically used in AUD screening may be too high in males with class 3 obesity. Abstract : For males and females, the odds of alcohol use disorder were higher with greater alcohol use. Among females, at the same frequency of any alcohol use, those with healthy weight had the highest odds of alcohol use disorder, while females with class 3 obesity had the lowest odds of alcohol use disorder ( p for interaction <0.001); interactions between weight status and frequency of any alcohol use was not significant among males ( p = 0.36).